Some Aspects of The Biology and Dynamics of the Blue- Spotted Sea Bream, Sparus Caeruleostictus in Ghanaian Waters - Owusu-Boateng, K. (University of Ghana, 1994)
This study, undertaken during the period March, 1992 - March, 1993, investigated the distribution, growth, population parameters, dynamics, food habits and reproduction of Sparus caeruleostictus in Ghanaian coastal waters - S.caeruleostictus show a distinctive size distribution by depth; bigger fish are found in deeper waters - There are two spawning periods in a year and new recruits come into the exploited population in their first year of life. S.caeruleostictus mature in their second year of life. Crustaceans are the main diet for the species. Growth and mortality parameters, as estimated with the Electronic Length Frequency Analysis (ELEFAN) methods are: LCTO = 44.3 cm (fork length), K = 0.48/yr., Z = 2.480/yr., M= 0.856 and F= 1.621/yr. The mean length at first capture, LC50 was estimated to be 10.75 cm (fork length) and the rate of exploitation E, 0.65. The lengths at first maturity for the males and females, were 18.4cm and 17.2cm (fork length) respective1y. Fecundity ranged from 4 0,000 — 400,000 (size range: 17.5 - 24.8cm fork length). Length and fecundity relationship was exponential and described by the equation: Log F = 1.3671 + 2.9479 Log L. Analysis of the relative yield per recruit (Y/R)’ showed that to achieve the maximum sustainable yield (MSY) it will be necessary to reduce the level of the present fishing effort.